Relationship Between Weaning Age and Nutritional Status of 2-Year-Old Toddlers - Nugroho Aning Pramuka; Yessy Nur Endah Sary; Iit Ermawati; Nova Hikmawati (KHD Production, 2023)
Weaning is the process of stopping breastfeeding gradually or all at once. The weaning process is recommended around the age of 2 years on the grounds that breastfeeding for more than 2 years has reduced nutrition. The research aims to identify the relationship between weaning age and the nutritional status of 2-year-old toddlers This research is a descriptive-analytic study, while the research design is cross-sectional. The data were taken from the data form of mothers and children who visited the integrated health service in the village, Pos Pelayanan Terpadu (Posyandu) Melati, Pasirian Village, Lumajang which was held on August 9, 2022, with a total population of 50 toddlers, the sample studied was 50 toddlers (Total Sampling). The data in this study were analyzed by univariate analysis and bivariate analysis using the Chi-Square Tests with a value obtained p=0.000, which means that there is a relationship between weaning age and the nutritional status of toddlers aged 2 years at Posyandu Melati, Pasirian Village, Lumajang Regency. So improper weaning results in low nutritional intake received by children aged 2 years. Likewise, children who have started to be weaned must pay special attention so that the nutrition that the child gets is sufficient.